Abrus agglutinin suppresses human hepatocellular carcinoma in vitro and in vivo by inducing caspase-mediated cell death - Mukhopadhyay, Subhadip (Nature Publishing Group, 2014)
AIM: Abrus agglutinin (AGG) from the seeds of Indian medicinal plant Abrus precatorius belongs to the class II ribosome inactivating protein family. In this study we investigated the anticancer effects of AGG against human hepatocellular carcinoma in vitro and in vivo. METHODS: Cell proliferation, DNA fragmentation, Annexin V binding, immunocytofluorescence, Western blotting, caspase activity assays and luciferase assays were performed to evaluate AGG in human liver cancer cells HepG2. Immunohistochemical staining and TUNEL expression were studied in tumor samples of HepG2-xenografted nude mice. RESULTS: AGG induced apoptosis in HepG2 cells in a dose- and time-dependent manner. AGG-treated HepG2 cells demonstrated an increase in caspase 3/7, 8 and 9 activities and a sharp decrease in the Bcl-2/Bax ratio, indicating activation of a caspase cascade. Co-treatment of HepG2 cells with AGG and a caspase inhibitor or treatment of AGG in Bax knockout HepG2 cells decreased the caspase 3/7 activity in comparison to HepG2 cells exposed only to AGG. Moreover, AGG decreased the expression of Hsp90 and suppressed Akt phosphorylation and NF-κB expression in HepG2 cells. Finally, AGG treatment significantly reduced tumor growth in nude mice bearing HepG2 xenografts, increased TUNEL expression and decreased CD-31 and Ki-67 expression compared to levels observed in the untreated control mice bearing HepG2 cells. CONCLUSION: AGG inhibits the growth and progression of HepG2 cells by inducing caspase-mediated cell death. The agglutinin could be an alternative natural remedy for the treatment of human hepatocellular carcinomas.